Peran Epistemologis Hadis dalam Melengkapi dan Mengkhususkan Ketentuan Ayat-Ayat Hukum Waris Islam (CV. Era Digital Nusantara, 2025)
This study explores the epistemological role of Prophetic Hadith in interpreting the quantitative inheritance provisions of the Qur’an, specifically Q.S. al-Nisa’ 11–12. Using a normative-analytical qualitative approach through library research, the research demonstrates that despite the detailed nature of Qur’anic verses, Hadith remains an indispensable legal source. It fills normative gaps through mechanisms such as clarifying residual estate distribution, identifying legal impediments, and limiting bequests. The findings reveal that Hadith's authority is derived not only from its chain of transmission but also from its coherence with the Qur'an, juristic consensus, and maqasid al-shari’ah. The article analyzes four primary functions: Bayan al-Tafsil, Takhsis al-’Amm, Taqyid al-Mutlaq, and the integration of specific weak traditions supported by consensus. Ultimately, this study affirms that the integration of the Qur’an and Hadith constitutes a vital epistemological foundation for achieving justice and systematic implementation within Islamic inheritance law. This internal synergy ensures that legal application remains equitable.